A new conceptual framework for a general theory of economic development: epistemological foundation and economic sustainability - Soto Llosa, Ignacio J. (1987)
​In the first part of this work "The Economic Development of Nations, a New Outlook?" in Apuntes 18, a, new conceptual framework was proposed by reconceptualizing Capital restricting it strictly to its material aspects, and Labour, empahasizing the role of the human factor by separating this concept in two: Labour in a restricted sense, and Steering, where the last concept embodies the economic activity of managers, decision makers, researchers but also of those who keep and disseminate knowledge and those who lead and govern. The concept of wealth is reformulated accordingly. The possible novelty of the idea and its place among the different currents of economic thought was also discussed. In this second part, the proposal is first supported showing it fulfills two tenets of neorealist philosophy of science applied to the social sciences: to demonstrate the good matching with reality of the concepts chosen as causal factors by making explicit its structure and to use when possible a paramorphic rather than a homeomorphic model (the last being the type mostly used in Economics), because of the former's greater intrinsic capacity to explain. The proposal is then fundamented from an economic point of view showing that the selection of causal factors proposed is not only epistemologically correct because it makes explicit the generative mechanisms operating in each case, but it fits well and in a coherent way the present reality of the world economy, both in its microeconomic aspects (the Firm according to recent developments of Organization Theory) and in its macroeconomic aspects (the economic development of Nation States and economic intercourse among them). It is also shown that the proposed causal factors can be measured although some adjustments in accounting procedures would be requiered. Finally, how the author proposes to outline, in a second phase, a General Theory of Economic Development is also discussed.